They Make a Desert and Call it Peace - Frank Carrigan (Legal Education Review)
Our paper seeks to begin a conversation about how legal academics might work collaboratively to resist neoliberal reforms in legal education. We begin by considering the existing literature about how academics have responded to recent efforts to corporatize university education. This literature reveals a great level of despondency and despair. Most acts of resistance are either individual or passive. Following this, we put forward as alternative conceptualisation of the academic – the academic activist. We consider whether this conceptualisation might offer a place from which resistance can emerge. Finally, we consider strategies that might be adopted by legal academics who wish to contest neoliberalism within the law school and the university. Given the evidence of academic despair and disempowerment, we propose a range of strategies which are both active and passive and range from the individual to the collaborative.